ECONOMIC CRISES IN MALAYSIA CAUSES, IMPLICATIONS & POLICY PRESCRIPTIONS - Okposin, Samuel Bossey; Cheng, Ming Yu (Pelanduk Publications, 2000)
This study identifies the various economic crises that has plagued Malaysia since 1957. Besides examining theorectical debates and causes of each of these crises, it also discusses the economic impact of each of these crises in relation to the economy and looks at the policy measure adopted for each crisis.